Analisis Pengaruh Struktur Modal Terhadap Return On Equtiy Perusahaan Pembiayaan (Studi Kasus Laporan Keuangan PT ABC 2007-2011) - , Putri Kinanti, Prof. Dr. Slamet Sugiri, MBA., Akt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Debt is oftenly used by many companies to raise its capital. This would make debt as one factor that effect companyâs profitability. This study uses the ratio of companyâs debts, the cost of capital, and macroeconomic factors to help understand the effect of debt to profitability in multifinance companies in Indonesia. Companyâs debts ratio are illustrated by Debt to Asset Ratio and Debt to Equity Ratio. Both of these ratios show the efficiency and effectiveness of the company in utilizing its debts to increase assets and its financial resources to generate profit. Cost of capital is described by calculating the perspective cost of weighted firmâs capital component. Minimization of capital costs would maximize the profits of the company. While macroeconomics factor is proxy by BI rate as a reference of banksâ interest rates. The results showed no significant effect of ratios of debt to the company's profitability, while result of cost of capital and interest rate support the research hypotheses that both factors negatively affect the company's profitability.